ANALISIS WIRELESS POWER TRANSMISSION SYSTEM DALAM ASPEK REGULASI MENGGUNAKAN METODE BENCHMARK - Samsurizal Samsurizal (Sekolah Tinggi Teknik - PLN, 2018)
Wireless technology has developed very rapidly both in terms of providing infrastructure and supporting technology that is on the side of the mobile computing device that has been widely used by people. Charging the battery is one of the primary needs of modern society. To support community activities that the higher the level of mobility, power bank is a solution. However, the ability of power banks are still limited in terms of charging. Thus, the wireless charging technology, or better known as the Wireless Power Transmission (WPT). Wireless Power Transmission is a technology that allows electrical energy from the power source to an electrical load is transmitted without any interconnection. Wireless Power Transmission especially useful for devices connected to the cable dangerous. This is new technology but the market has seen demand increase significantly. Various types of applications, that the technology Wireless Power Transmission (WPT) is applied, the expected and the study of the current WPT is underway. Also, ongoing standardization activities in several standardization organizations.as well as the issuance of Wireless Power Transmission Regulations in some countries so expect the harmonization of rules / law in the implementation of Wireless Power Transmission in everyday life, Clarity and certainty of legal framework for the implementation of the regulatory function of the business operations of Wireless Power Transmission.